Hubungan Status Gizi Ibu Hamil Trimester III Dengan Anemia Di BPM Erlina Herawati Tahun 2023 - Nurmalina Hutahaen; Yanti Rosmidar Hasibuan (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
According to the World Health Organization (WHO) in 2015, the prevalence of anemia in pregnant women ranged from 20% to 89%, with 11 grams set as the threshold. The study findings reveal a significant association between nutritional status and anemia in pregnant women. The majority of respondents were at risk of poor nutritional status (54.3%), while 45.7% experienced anemia. Among those with adequate nutritional status, 34.3% did not have anemia, whereas 65.7% did. The majority of anemia cases were associated with at-risk nutritional status (54.3%), while none of the non-anemic pregnant women were at risk. Among those with adequate nutritional status, 34.3% did not have anemia, compared to 11.4% who did. The Chi-Square statistical analysis yielded a p-value of 0.000 < 0.05, indicating a significant relationship between nutritional status and anemia in pregnant women. It is recommended that healthcare providers pay closer attention to pregnant women's nutritional status through antenatal care visits.